Safety-II and Resilience Engineering in a Nutshell: An Introductory Guide to Their Concepts and Methods - Dong-Han Ham (Elsevier, 2021)
Background: Traditional safety concept, which is called Safety-I, and its relevant methods and models have much contributed toward enhancing the safety of industrial systems. However, they have proved insufficient to be applied to complex socio-technical systems. As an alternative, Safety-II and resilience engineering have emerged and gained much attention for the last two decades. However, it seems that safety professionals have still difficulty understanding their fundamental concepts and methods. Accordingly, it is necessary to offer an introductory guide to them that helps safety professionals grasp them correctly in consideration of their current practices. Methods: This article firstly explains the limitations of Safety-I and how Safety-II can resolve them from the four points of view. Next, the core concepts of resilience engineering and Functional Resonance Analysis Method are described. Results: Workers' performance adjustment and performance variability due to it should be the basis for understanding human-related accidents in socio-technical systems. It should be acknowledged that successful and failed work performance have the same causes. However, they are not well considered in the traditional safety concept; in contrast, Safety-II and resilience engineering have conceptual bases and practical approaches to reflect them systematically. Conclusion: It is necessary to move from a find-and-fix and reactive approach to a proactive approach to safety management. Safety-II and resilience engineering give a set of useful concepts and methods for proactive safety management. However, if necessary, Safety-I methods need to be properly used for situations where they can still be useful as well.